A hydrogel-coated titanium implant, its preparation method and application
Patent Information
- Application Number
- CN202611357039.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-30
AI Technical Summary
初期,巨噬细胞会极化形成M1型促炎表型,并分泌大量促炎因子,以清除残留病原体和组织碎片,若M1表型持续存在,会导致种植体周围慢性炎症,进而阻碍骨愈合并削弱种植体稳定性
本发明通过在表面硅烷化钛基体包覆含有硅酸镁锂的热敏水凝胶层,第一方面,利用热敏水凝胶层的高含水量、良好的生物相容性和可控的机械性能模拟细胞外基质,增强种植体表面的细胞黏附与浸润;第二方面,作为硅酸镁锂的储存和释放平台,实现对局部骨修复微环境的持续调控;第三方面,硅酸镁锂释放Li+、Mg2+和Si(OH)4相关生物活性组分,促使M1型巨噬细胞极化为M2型抗炎表型,M2型巨噬细胞分泌多种活性因子,这些细胞因子可营造抗炎微环境,从而加速组织修复,促进骨再生和血管生成;第四方面,热敏水凝胶层在体温环境因温敏响应而收缩,致密化热敏水凝胶层,提高涂层结构稳定性和强化对钛基体的包覆效果,并且通过表面硅烷化引入的活性双键,原位自由基聚合在钛基体表面进一步提高热敏水凝胶层与钛基体的界面结合稳定性。综合作用下,提高了钛种植体的细胞相容性、界面结合稳定性、涂层结构稳定性、免疫调控能力和促成骨作用,有利于促进种植体周围新骨形成和骨-种植体界面整合,适合在牙科种植体、骨科植入物及骨修复材料等产品方面的应用。
Smart Images

Figure CN122998461A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical materials, and in particular to a hydrogel-coated titanium implant, its preparation method, and its application. Background Technology
[0002] Titanium and titanium alloys are widely used in dental implants, orthopedic implants, and joint replacements due to their good biocompatibility, excellent mechanical properties, and strong corrosion resistance. However, the elastic modulus of titanium and titanium alloys is significantly higher than that of natural bone tissue, which can easily induce a stress shielding effect after implantation, leading to insufficient stress on surrounding bone tissue, increased bone resorption, and affecting the long-term stability of titanium implants. At the same time, the strong bioinertness of titanium surfaces limits osseointegration efficiency. Therefore, improving the bioactivity of titanium implant surfaces is a crucial technical problem that urgently needs to be solved in the field of titanium implant materials.
[0003] To improve the osseointegration performance of titanium implants, various surface modification strategies have been proposed, including sandblasting, acid etching, laser treatment, anodizing, and the construction of micro / nano structures. These methods primarily improve cell adhesion and osteoconductive properties by controlling the micro / nano morphology, roughness, and surface energy of the titanium implant surface, thereby promoting the integration of bone tissue and the implant to a certain extent. However, relying solely on surface morphology control has limited ability to actively regulate the local biological microenvironment, and a rougher surface structure can increase the risk of bacterial colonization to some extent. Other studies have attempted to actively regulate the bone repair microenvironment by delivering bioactive molecules such as bone morphogenetic proteins, but these bioactive molecules suffer from degradation, poor stability, and high raw material costs, limiting their further application. Furthermore, after titanium implantation, the body rapidly initiates an acute inflammatory response. Neutrophils are rapidly recruited to the injury site to clear necrotic tissue debris and pathogens, followed by monocytes migrating to the implantation area and differentiating into macrophages. Macrophages exhibit high plasticity and can display pro-inflammatory M1 or anti-inflammatory M2 phenotypes under different microenvironmental stimuli. Initially, macrophages polarize to form the M1 pro-inflammatory phenotype and secrete a large number of pro-inflammatory factors to clear residual pathogens and tissue debris. If the M1 phenotype persists, it will lead to chronic inflammation around the implant, which will hinder bone healing and weaken implant stability. Summary of the Invention
[0004] In view of the shortcomings of the above-mentioned related technologies, the present invention provides hydrogel-coated titanium implants, their preparation methods and applications.
[0005] In a first aspect, the hydrogel-coated titanium implant provided by the present invention adopts the following technical solution: A hydrogel-coated titanium implant includes a surface silanized titanium substrate and a thermosensitive hydrogel layer covering the surface silanized titanium substrate, wherein the thermosensitive hydrogel layer is doped with lithium magnesium silicate.
[0006] Preferably, the surface silanized titanium matrix is prepared by the following steps: immersing the surface hydroxylated titanium matrix in a silane coupling agent solution for 12-36 hours and then washing it.
[0007] Preferably, the surface-hydroxylated titanium matrix is prepared by the following steps: after cleaning the titanium matrix, it is immersed in an aqueous sulfuric acid solution for 0.5-1.5 hours, then transferred to a hydroxylation reagent for immersion for 0.5-1.5 hours, and washed to obtain the surface-hydroxylated titanium matrix; the hydroxylation reagent is prepared by mixing concentrated sulfuric acid and an aqueous hydrogen peroxide solution in a volume ratio of 2.5-5:1.
[0008] Preferably, the thermosensitive hydrogel layer is obtained by free radical polymerization of a hydrogel precursor solution, wherein the hydrogel precursor solution comprises lithium magnesium silicate and N-isopropylacrylamide in a weight ratio of 0.2-0.4:1.
[0009] Preferably, the free radical polymerization includes using potassium persulfate as an initiator and N,N,N',N'-tetramethylethylenediamine as a promoter, and polymerizing in a sealed oven at 37-50°C for 3-8 hours under nitrogen protection.
[0010] Preferably, the lithium magnesium silicate in the hydrogel precursor solution has a mass-volume fraction of 2%-4%; and the N-isopropylacrylamide in the hydrogel precursor solution has a mass-volume fraction of 8%-12%.
[0011] Secondly, the method for preparing a hydrogel-coated titanium implant provided by the present invention adopts the following technical solution: A method for preparing a hydrogel-coated titanium implant includes the following steps: S1. The titanium matrix is washed sequentially with acetone, ethanol and deionized water to obtain a pretreated titanium matrix. S2. After acid leaching, the pretreated titanium matrix is subjected to surface hydroxylation treatment to obtain a surface-hydroxylated titanium matrix. S3. The surface hydroxylated titanium matrix is immersed in a silane coupling agent solution and then washed to obtain a surface silanized titanium matrix. S4. Take lithium magnesium silicate, N-isopropylacrylamide, initiator, accelerator and solvent and mix them evenly in an inert atmosphere to obtain hydrogel precursor solution; S5. Immerse the surface silanized titanium substrate in a hydrogel precursor solution and perform free radical polymerization until a dense thermosensitive hydrogel layer is formed on the surface of the surface silanized titanium substrate to obtain the hydrogel-coated titanium implant.
[0012] Preferably, step S4 includes the following steps: mixing lithium magnesium silicate with a portion of the solvent to obtain a lithium magnesium silicate dispersion, pre-dissolving the initiator in another portion of the solvent to obtain an initiator solution, and mixing the lithium magnesium silicate dispersion, N-isopropylacrylamide, the initiator solution, and the accelerator uniformly in an inert atmosphere to obtain a hydrogel precursor solution.
[0013] Preferably, the initiator has a mass-volume fraction of 0.2%-0.4% in the hydrogel precursor solution, and the accelerator accounts for 0.08%-0.2% of the solvent volume.
[0014] Thirdly, the present invention provides the application of the above-described hydrogel-coated titanium implant or the hydrogel-coated titanium implant prepared by the above-described method in the preparation of dental implants, orthopedic implants or bone repair materials.
[0015] In summary, the present invention has at least one of the following beneficial technical effects: This invention utilizes a thermosensitive hydrogel layer containing lithium magnesium silicate to coat a surface-silanized titanium substrate. Firstly, the high water content, good biocompatibility, and controllable mechanical properties of the thermosensitive hydrogel layer mimic the extracellular matrix, enhancing cell adhesion and infiltration on the implant surface. Secondly, it serves as a storage and release platform for lithium magnesium silicate, enabling continuous regulation of the local bone repair microenvironment. Thirdly, lithium magnesium silicate releases Li... + Mg 2+ The bioactive components related to Si(OH)4 induce M1 macrophages to polarize into the M2 anti-inflammatory phenotype. M2 macrophages secrete various active factors, which create an anti-inflammatory microenvironment, thereby accelerating tissue repair and promoting bone regeneration and angiogenesis. Fourthly, the thermosensitive hydrogel layer shrinks in response to body temperature, densifying the layer and improving coating structural stability and coating effect on the titanium matrix. Furthermore, the active double bonds introduced through surface silanization further enhance the interfacial bonding stability between the thermosensitive hydrogel layer and the titanium matrix through in-situ free radical polymerization. These combined effects improve the cell compatibility, interfacial bonding stability, coating structural stability, immunomodulatory capacity, and osteogenic effect of titanium implants, promoting new bone formation around the implant and bone-implant interface integration. This makes it suitable for applications in dental implants, orthopedic implants, and bone repair materials. Attached Figure Description
[0016] Figure 1 These are macroscopic morphology comparison diagrams of Example 1, Comparative Example 1, Experimental Example 1, and Experimental Example 2; Figure 2 These are comparison images of the microstructures of Example 1, Comparative Example 1, Experimental Example 1, and Experimental Example 2; Figure 3These are the Fourier transform infrared spectra of Example 1, Comparative Example 1, Test Example 1, and Test Example 2; Figure 4 This is the result of the change in the ratio of the sample mass to the initial mass after soaking under different temperature conditions in Example 1 as a function of soaking time; Figure 5 These are the rheological properties test results of the thermosensitive hydrogel layer in Example 1; Figure 6 This refers to Li after soaking at different temperatures in Example 1. + Mg 2+ and Si 4+ Results of cumulative release over time; Figure 7 The results of immunofluorescence staining of CD86, a marker of M1 macrophage, and CD206, a marker of M2 macrophage, after co-culturing RAW 264.7 macrophages with Comparative Example 1 and Example 1, respectively; Figure 8 The results of alkaline phosphatase staining, alizarin red S staining, and corresponding quantitative analysis of osteogenic differentiation of bone marrow mesenchymal stem cells in Comparative Example 1 and Example 1 are as follows: Figure 9 HE staining results at the implantation site in the rat femoral implantation model of Comparative Example 3 and Example 2; Figure 10 The results of Masson's trichrome staining at the implantation site in the rat femoral implantation model of Comparative Example 3 and Example 2 are shown. Figure 11 The results show the morphological and quantitative analysis of new bone tissue around the implantation site in the rat femoral implantation model of Comparative Example 3 and Example 2. Detailed Implementation
[0017] The present invention will be further described in detail below with reference to the embodiments. The following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified, specific conditions in the following embodiments were performed under conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, the methods used are conventional methods known in the art, and the consumables and reagents used are commercially available. Unless otherwise stated, the technical and scientific terms used herein have the same meaning as those familiar to those skilled in the art. Furthermore, any methods or materials similar to or equivalent to those described herein may also be applied to the present invention.
[0018] Example 1 Example 1 of this invention provides a hydrogel-coated titanium implant, the preparation method of which is as follows: S1. Take a circular titanium sheet (14.8 mm in diameter and 1 mm in thickness), and place it in acetone, ethanol and deionized water for ultrasonic washing in sequence. After washing, place it in a 37°C oven to dry, and obtain a pretreated titanium matrix for later use.
[0019] S2. The pretreated titanium substrate was immersed in an 80% (v / v) sulfuric acid aqueous solution for 1 hour and then washed three times with deionized water. A hydroxylation reagent was prepared by mixing 98% concentrated sulfuric acid and 30% hydrogen peroxide aqueous solution in a volume ratio of 3:1. The pretreated titanium substrate was then immersed in the hydroxylation reagent for 1 hour to introduce hydroxyl groups onto the surface of the titanium substrate. Finally, it was washed with deionized water and ethanol in sequence to obtain a surface-hydroxylated titanium substrate.
[0020] S3. The surface hydroxylated titanium matrix was immersed in a silane coupling agent solution (an ethanol solution with a volume fraction of 10% propyl 3-(trimethoxysilyl)methacrylate) for 24 hours, and then washed three times with ethanol to obtain a surface silanized titanium matrix.
[0021] S4. Mix 0.3g of lithium magnesium silicate (Lap) with 9mL of deionized water and stir magnetically until uniformly dispersed to obtain a lithium magnesium silicate dispersion. Dissolve 0.03g of potassium persulfate (K2S2O8) initiator in 1mL of deionized water to obtain an initiator solution. Add 1g of N-isopropylacrylamide (PNIPAM) to the lithium magnesium silicate dispersion and stir magnetically for 1h. Under ice bath conditions, add the initiator solution and 10μL of N,N,N',N'-tetramethylethylenediamine (TEMED) accelerator, stir magnetically for 10 minutes, and purge with nitrogen gas throughout to obtain the hydrogel precursor solution.
[0022] S5. Immerse the surface silanized titanium substrate in the hydrogel precursor solution for 2 minutes, then remove it, seal it under nitrogen protection, and place it in a 37°C oven for polymerization for 8 hours to obtain the hydrogel-coated titanium implant.
[0023] Example 2 Example 2 of the present invention provides a hydrogel-coated titanium implant. The difference between Example 2 and Example 1 is that in the preparation process of Example 2, titanium nails (1 mm in diameter and 3 mm in length) are used instead of circular titanium sheets as titanium substrate.
[0024] Comparative Example 1 Comparative Example 1 provides a titanium sheet, which uses the pretreated titanium matrix obtained in step S1 of the preparation process in Example 1.
[0025] Comparative Example 2 Comparative Example 2 provides a titanium sheet using the surface-silanized titanium substrate obtained in step S3 of Example 1.
[0026] Comparative Example 3 Comparative Example 3 provides a titanium nail, which uses the pretreated titanium matrix obtained in step S1 of the preparation process in Example 2.
[0027] Testing and Inspection (1) Characterization of the surface morphology and structure of the thermosensitive hydrogel layer: Analysis of physical images: Since PNIPAM hydrogel is a typical thermosensitive hydrogel, its lower critical dissolution temperature is approximately 32°C. Below this temperature, the hydrogel is in a state of relative water absorption and swelling; above this temperature, the hydrogel undergoes water loss and shrinkage. To verify whether the thermosensitive hydrogel layer of the hydrogel-coated titanium implant was successfully constructed and to evaluate the changes in surface morphology and structure of the hydrogel coating at different temperatures, the hydrogel-coated titanium implant prepared in Example 1 was immersed in deionized water at 25°C and 37°C for the same amount of time, respectively, resulting in Experimental Example 1 and Experimental Example 2. The macroscopic morphology comparison figures of Comparative Example 1, Comparative Example 2, Experimental Example 1, and Experimental Example 2 are shown below. Figure 1 As shown, they are labeled as Ti, Ti-TMSPMA, PNIPAM / Lap-Ti (25℃) and PNIPAM / Lap-Ti (37℃) in sequence.
[0028] Reference Figure 1 From a macroscopic perspective, a continuous heat-sensitive hydrogel layer was successfully formed on the surface of the titanium substrate. After being immersed at 37°C, the heat-sensitive hydrogel layer on the surface of the titanium implant in Experiment Example 2 changed from a relatively transparent state to a milky white state, showing a macroscopic signal of a temperature-sensitive phase transition. The increase in opacity indicates that the heat-sensitive hydrogel layer shrinks and densifies under the treatment at 37°C.
[0029] Analysis of scanning electron microscope images: The samples from Experimental Example 1 and Experimental Example 2 were rapidly frozen in liquid nitrogen for freeze-drying. The microstructure of the surfaces of Comparative Example 1, Comparative Example 2, Experimental Example 1, and Experimental Example 2 was then observed. Scanning electron micrographs are shown below. Figure 2 As shown, they are labeled as Ti, Ti-TMSPMA, PNIPAM / Lap-Ti (25℃) and PNIPAM / Lap-Ti (37℃) in sequence.
[0030] Reference Figure 2The results showed that the Ti group had a relatively smooth surface with obvious shallow marks from polishing. The surface morphology of the Ti-TMSPMA group was similar to that of the Ti group, indicating that the TMSPMA modification mainly occurred at the molecular level on the surface of the titanium substrate. Compared with the Ti group and Ti-TMSPMA, the PNIPAM / Lap-Ti (25℃) and PNIPAM / Lap-Ti (37℃) samples both showed thermosensitive hydrogel layer coverage, indicating that the thermosensitive hydrogel layer was successfully constructed on the surface of the silanized titanium substrate. After treatment at 25℃, the surface of Example 1 showed a relatively loose coverage morphology, while after treatment at 37℃, the surface of Example 1 showed more obvious shrinkage and wrinkling structures, further indicating that the thermosensitive hydrogel layer of the titanium implant with hydrogel coating in Example 1 can be further densified in vivo to improve the stability of the coating structure and enhance the coating effect on the titanium substrate.
[0031] Fourier transform infrared spectroscopy analysis: The samples from Test Example 1 and Test Example 2 were rapidly frozen in liquid nitrogen for freeze-drying. Then, the Fourier transform infrared spectra of Comparative Example 1, Comparative Example 2, Test Example 1, and Test Example 2 were measured. Figure 3 As shown, they are labeled as Ti, Ti-TMSPMA, PNIPAM / Lap-Ti (25℃), and PNIPAM / Lap-Ti (37℃) in sequence. Figure 3 B is Figure 3 A magnified view of part A in the image; Reference Figure 3 The results showed that the infrared absorption peak of Comparative Example 1 was weak, and no obvious characteristic peaks of organic functional groups appeared; after modification with TMSPMA, Comparative Example 2 showed an ester group C=O stretching vibration peak at approximately 1716 cm⁻¹, and a peak at approximately 1634 cm⁻¹. - The presence of a C=C stretching vibration peak at position ¹ indicates that TMSPMA has successfully modified the titanium matrix surface; both Samples from Experimental Example 1 and Experimental Example 2 exhibit characteristic absorption peaks of PNIPAM, with the peak at approximately 1637 cm⁻¹ being the most prominent. - The absorption peak at ¹ can be attributed to the amide I band in PNIPAM, and the absorption peak near ¹ can be attributed to the amide II band in PNIPAM, around 1458 cm⁻¹. - ¹、1387cm - ¹ and 1368cm - The absorption peaks near ¹ can be attributed to the CH bending vibration and related characteristic vibrations of the isopropyl group in PNIPAM.
[0032] (2) Evaluation of coating stability and rheological properties: To evaluate the coating stability and rheological properties of the hydrogel-coated titanium implant in Example 1, the following tests were conducted to assess the mass change of the thermosensitive hydrogel layer and its rheological properties.
[0033] Test for changes in the mass of the thermosensitive hydrogel layer: The hydrogel-coated titanium implant from Example 1 was immersed in 10 mL of phosphate-buffered saline (pH=7.4) at 25°C and 37°C for 60 days. Samples were removed at multiple time points during this period, residual liquid on the sample surface was gently removed with filter paper, and the samples were weighed. The samples were then returned to the PBS solution for further immersion. The change in the ratio of sample mass to initial mass over immersion time was obtained, as shown in the figure. Figure 4 As shown, the quality changes and stability of the thermosensitive hydrogel layer of the hydrogel-coated titanium implant in Example 1 were evaluated under different temperature conditions.
[0034] Reference Figure 4 The results showed that at 25℃, the sample mass ratio gradually increased with prolonged soaking time and then stabilized, indicating that the hydrogel network was in a relatively hydrophilic and swollen state. Conversely, at 37℃, the sample mass ratio decreased initially and then stabilized, indicating that the hydrogel network of the thermosensitive hydrogel layer shrank and reduced excessive water absorption. This demonstrates that the thermosensitive hydrogel layer in Example 1 of this invention can reduce excessive swelling of the hydrogel under body temperature conditions, which is beneficial for maintaining the stability of the coating structure, consistent with the morphology and structural characterization results.
[0035] Rheological property evaluation of hydrogel coatings: The amplitude scanning test of the thermosensitive hydrogel layer of the hydrogel-coated titanium implant in Example 1 was performed using a rheometer, and the results are as follows: Figure 5 As shown in Figure A; a temperature scan test was performed, and the results are as follows. Figure 5 As shown in Figure B; a frequency scan test was performed, and the results are as follows. Figure 5 As shown in C.
[0036] Reference Figure 5 In Figure A, the results show that within the strain range of 0.1%-30%, the storage modulus of the thermosensitive hydrogel layer remains relatively stable and is higher than the loss modulus, indicating that the hydrogel exhibits a predominantly elastic response and a stable three-dimensional network structure within this range. When the strain increases to 100%, the storage modulus decreases to near the loss modulus, suggesting that the hydrogel network is disrupted. (Reference) Figure 5 In Figure B, the results showed that at a temperature of 32℃, the storage modulus of the thermosensitive hydrogel layer increased with rising temperature, indicating that the thermosensitive hydrogel layer exhibited mechanical enhancement during the heating process. (Reference) Figure 5 The results showed that, within the test frequency range of 0.1-50Hz, the thermosensitive hydrogel layer exhibited a higher storage modulus than loss modulus, indicating that the thermosensitive hydrogel layer has gel properties dominated by elasticity and a stable network structure.
[0037] (3) Li hydrogel coating + Mg2+ Evaluation of Si(OH)4 release performance: The hydrogel-coated titanium implant from Example 1 was immersed in 20 mL of PBS buffer (pH=7.4) at 37°C and 25°C, respectively. On days 1, 5, 15, and 30, 10 mL of the liquid was aspirated, filtered through a 0.45 μm filter membrane, and then 10 mL of fresh PBS buffer was added. The Li content in the sampled liquid was detected using inductively coupled plasma optical emission spectrometry (ICP-OES). + Mg 2 + and Si 4+ The content of Li is given as a cumulative release value, calculated as the average of three replicates at different temperatures. + The cumulative release over time results are as follows: Figure 6 As shown in Figure A, Mg at different temperatures 2+ The cumulative release over time results are as follows: Figure 6 As shown in Figure B, Si at different temperatures 4+ The cumulative release over time results are as follows: Figure 6 As shown in C.
[0038] Reference Figure 6 The results showed that the hydrogel-coated titanium implant of Example 1 continuously released Li during the soaking process. + Mg 2 + The release curves of the bioactive components related to Si(OH)4 under different temperature conditions show a similar overall trend, indicating that the hydrogel-coated titanium implant of Example 1 can maintain the ability to continuously release bioactive components under different temperature conditions.
[0039] (4) Evaluation of immune regulation performance: RAW 264.7 macrophages were divided into four groups: Control, LPS, LPS+Ti, and LPS+PNIPAM / Lap-Ti. The Control group served as the normal culture control group. The LPS group received LPS to induce macrophage inflammatory activation. The LPS+Ti group received LPS along with titanium sheets from Comparative Example 1 for co-culture. The LPS+PNIPAM / Lap-Ti group received LPS along with hydrogel-coated titanium implants from Example 1 for co-culture. Immunofluorescence staining was used to detect the expression of CD86, a marker of M1 macrophages, and CD206, a marker of M2 macrophages. The results are as follows: Figure 7 As shown in Figure A, the fluorescence intensity was quantitatively analyzed. The results of the quantitative analysis of the fluorescence intensity of CD86, a marker of M1 macrophages, are as follows. Figure 7 As shown in Figure B, the quantitative analysis results of the fluorescence intensity of CD206, a marker of M2 macrophages, are as follows: Figure 7As shown in C.
[0040] Reference Figure 7 The results showed that CD86 expression was low in the Control group; after LPS stimulation, CD86 fluorescence was significantly enhanced and CD206 expression was reduced in the LPS group, indicating that LPS successfully induced RAW 264.7 macrophages to polarize towards the pro-inflammatory M1 phenotype; compared with the LPS group, CD86 expression in the LPS+Ti group remained at a high level, while CD206 expression did not show a significant increase; compared with the LPS+Ti group, the CD86 fluorescence intensity in the LPS+PNIPAM / Lap-Ti group was significantly reduced, while the CD206 fluorescence intensity was significantly increased, indicating that the hydrogel-coated titanium implant of Example 1 can inhibit macrophage polarization towards the M1 pro-inflammatory phenotype and promote its transformation towards the M2 anti-inflammatory repair phenotype, thereby creating an anti-inflammatory microenvironment.
[0041] (5) Evaluation of in vitro immunomodulatory osteogenic properties: RAW 264.7 macrophages were divided into four groups: Control, LPS, LPS+Ti, and LPS+PNIPAM / Lap-Ti. The Control group served as the normal culture control group. The LPS group received LPS to induce macrophage inflammatory activation. The LPS+Ti group received LPS along with titanium sheets from Example 1 for co-culture. The LPS+PNIPAM / Lap-Ti group received LPS along with hydrogel-coated titanium implants from Example 1 for co-culture. Conditioned culture media from each group were collected for culturing bone marrow mesenchymal stem cells. After 7 days of culture, alkaline phosphatase staining (ALP staining) was used to evaluate the early osteogenic differentiation capacity of bone marrow mesenchymal stem cells. After 14 days of culture, Alizarin Red S staining was used to evaluate extracellular matrix mineralization capacity. The staining results are shown below. Figure 8 As shown in Figure A, the quantitative analysis results of ALP staining are as follows: Figure 8 As shown in Figure B, the quantitative analysis results of Alizarin Red S staining are as follows: Figure 8 As shown in C.
[0042] Reference Figure 8 In ALP staining, the LPS+PNIPAM / Lap-Ti group showed significantly enhanced staining and an increased positive staining area, indicating enhanced early osteogenic differentiation capacity of bone marrow mesenchymal stem cells. In Alizarin Red S staining, the LPS+PNIPAM / Lap-Ti group showed a significant increase in red mineralized nodules and a marked increase in staining area, indicating enhanced extracellular matrix mineralization capacity. In summary, the macrophage conditioned medium regulated by the hydrogel-coated titanium implant of Example 1 is beneficial for promoting early osteogenic differentiation and matrix mineralization of bone marrow mesenchymal stem cells, verifying that the hydrogel-coated titanium implant of Example 1 has an immunomodulatory mediated osteogenic effect.
[0043] (6) Evaluation of in vivo osseointegration performance: Twenty healthy 8-week-old male SD rats were randomly divided into two groups: the Ti group and the PNIPAM / Lap-Ti group, with 10 rats in each group. All rats were anesthetized preoperatively with 5 mL / kg body weight of 1% sodium pentobarbital (Sigma Aldrich, USA) via intraperitoneal injection. The fur on the hind limbs was shaved, and the rats were placed in a supine position and fixed. A longitudinal incision was made in the skin of both hind limbs, and screws were implanted along the longitudinal axis of the femur into the femoral condyle. Eight weeks post-implantation, the rats were euthanized with sodium pentobarbital. Both femurs were harvested and fixed in 4% paraformaldehyde for hematoxylin-eosin (HE) staining, Masson's trichrome staining, and Micro-CT scanning. The Ti group received the titanium screws used in Comparative Example 3, while the PNIPAM / Lap-Ti group received the hydrogel-coated titanium implants used in Example 2.
[0044] Histological evaluation by HE and Masson's trichrome staining analysis: Femoral sections from the Ti group and the PNIPAM / Lap-Ti group were stained with hematoxylin and eosin (HE), and the results are as follows: Figure 9 As shown; Masson's trichrome staining was performed, and the results are as follows. Figure 10 As shown.
[0045] Reference Figure 9 The results showed that, compared with the titanium screw in Comparative Example 3, the hydrogel-coated titanium implant in Example 2 formed richer and more orderly new bone tissue around it; (Refer to...) Figure 10 The results showed that, compared with the titanium nail in Comparative Example 3, the collagen fiber deposition at the interface of the hydrogel-coated titanium implant in Example 2 was denser, indicating that it is beneficial to enhance extracellular matrix remodeling and promote bone regeneration.
[0046] Micro-CT 3D Reconstruction and Bone Morphometric Analysis: Micro-CT was used to scan and reconstruct the new bone tissue around the implantation site in the Ti group and the PNIPAM / Lap-Ti group. The results are as follows: Figure 11 As shown in Figure A; and a quantitative analysis was performed on the new bone formation in the area surrounding the implantation site, such as bone volume fraction, number of trabeculae, trabecular thickness, and trabecular spacing. The results are as follows. Figure 11 As shown in B.
[0047] Reference Figure 11 In Figure A, the results showed that compared with the Ti group, the PNIPAM / Lap-Ti group had significantly more peri-implant bone regeneration, and the bone tissue distribution around the implant was more continuous. This indicates that the hydrogel-coated titanium implant of Example 2 is beneficial for promoting peri-implant bone formation and improving bone tissue continuity. (Refer to...) Figure 11In Figure B, the results showed that the PNIPAM / Lap-Ti group had higher bone volume fraction, trabecular bone number, and trabecular bone thickness than the Ti group, while the trabecular bone spacing was smaller. This indicates that the hydrogel-coated titanium implant of Example 2 is beneficial for increasing the amount and density of new bone tissue formation. In summary, the hydrogel-coated titanium implant of Example 2 is beneficial for promoting new bone formation around the implant and improving the trabecular bone microstructure, thereby improving in vivo osseointegration performance.
[0048] This specific embodiment is merely an explanation of the present invention and is not intended to limit the invention. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they are within the scope of the claims of the present invention.
Claims
1. A hydrogel-coated titanium implant, characterized in that: It includes a surface-silanized titanium substrate and a thermosensitive hydrogel layer covering the surface-silanized titanium substrate, wherein the thermosensitive hydrogel layer is doped with lithium magnesium silicate.
2. The hydrogel-coated titanium implant according to claim 1, characterized in that: The surface silanized titanium matrix is prepared by the following steps: immersing the surface hydroxylated titanium matrix in a silane coupling agent solution for 12-36 hours and then washing it.
3. The hydrogel-coated titanium implant according to claim 2, characterized in that: The surface-hydroxylated titanium matrix is prepared by the following steps: after cleaning the titanium matrix, it is immersed in an aqueous sulfuric acid solution for 0.5-1.5 hours, then transferred to a hydroxylation reagent for immersion for 0.5-1.5 hours, and washed to obtain the surface-hydroxylated titanium matrix; the hydroxylation reagent is prepared by mixing concentrated sulfuric acid and an aqueous hydrogen peroxide solution in a volume ratio of 2.5-5:
1.
4. The hydrogel-coated titanium implant according to claim 1, characterized in that: The thermosensitive hydrogel layer is obtained by free radical polymerization of a hydrogel precursor solution, wherein the hydrogel precursor solution comprises lithium magnesium silicate and N-isopropylacrylamide in a weight ratio of 0.2-0.4:
1.
5. The hydrogel-coated titanium implant according to claim 4, characterized in that: The free radical polymerization involves using potassium persulfate as an initiator and N,N,N',N'-tetramethylethylenediamine as a promoter, and then sealing the mixture under nitrogen protection and placing it in an oven at 37-50°C for 3-8 hours for polymerization.
6. The hydrogel-coated titanium implant according to claim 4, characterized in that: The lithium magnesium silicate in the hydrogel precursor solution has a mass-volume fraction of 2%-4%; the N-isopropylacrylamide in the hydrogel precursor solution has a mass-volume fraction of 8%-12%.
7. A method for preparing a hydrogel-coated titanium implant as described in any one of claims 1-6, characterized in that: Includes the following steps: S1. The titanium matrix is washed sequentially with acetone, ethanol and deionized water to obtain a pretreated titanium matrix. S2. After acid leaching, the pretreated titanium matrix is subjected to surface hydroxylation treatment to obtain a surface-hydroxylated titanium matrix. S3. The surface hydroxylated titanium matrix is immersed in a silane coupling agent solution and then washed to obtain a surface silanized titanium matrix. S4. Take lithium magnesium silicate, N-isopropylacrylamide, initiator, accelerator and solvent and mix them evenly in an inert atmosphere to obtain hydrogel precursor solution; S5. Immerse the surface silanized titanium substrate in a hydrogel precursor solution and perform free radical polymerization until a dense thermosensitive hydrogel layer is formed on the surface of the surface silanized titanium substrate to obtain the hydrogel-coated titanium implant.
8. The method for preparing a hydrogel-coated titanium implant according to claim 7, characterized in that: Step S4 includes the following steps: mixing lithium magnesium silicate with a portion of the solvent to obtain a lithium magnesium silicate dispersion; pre-dissolving the initiator in another portion of the solvent to obtain an initiator solution; and mixing the lithium magnesium silicate dispersion, N-isopropylacrylamide, the initiator solution, and the accelerator uniformly in an inert atmosphere to obtain a hydrogel precursor solution.
9. The method for preparing a hydrogel-coated titanium implant according to claim 7, characterized in that: The initiator has a mass-volume fraction of 0.2%-0.4% in the hydrogel precursor solution, and the accelerator accounts for 0.08%-0.2% of the solvent volume.
10. The use of a hydrogel-coated titanium implant prepared by any one of claims 1-6 or any one of claims 7-9 in the preparation of dental implants, orthopedic implants or bone repair materials with immunomodulatory and osteogenic functions.
